Iron Recycle-Driven Organic Capture and Sidestream Anaerobic Membrane Bioreactor for Revolutionizing Bioenergy Generation in Municipal Wastewater Treatment - Ye, Min; Zhu, Aijun; Liu, Jianyong; Li, Yu-You (Environmental science & technology, 2024)
The practicality of intensifying organic matter capture for bioenergy recovery to achieve energy-neutral municipal wastewater treatment is hindered by the lack of sustainable methods. This study developed innovative processes integrating iron recycle-driven organic capture with a sidestream anaerobic membrane bioreactor (AnMBR). Iron-assisted chemically enhanced primary treatment achieved elemental redirection with 75.2% of chemical oxygen demand (COD), 20.2% of nitrogen, and 97.4% of phosphorus captured into the sidestream process as iron-enhanced primary sludge (Fe-PS). A stable and efficient biomethanation of Fe-PS was obtained in AnMBR with a high methane yield of 224 mL/g COD. Consequently, 64.1% of the COD in Fe-PS and 48.2% of the COD in municipal wastewater were converted into bioenergy. The acidification of anaerobically digested sludge at pH = 2 achieved a high iron release efficiency of 96.1% and a sludge reduction of 29.3% in total suspended solids. Ultimately, 87.4% of iron was recycled for coagulant reuse, resulting in a theoretical 70% reduction in chemical costs. The novel system evaluation exhibited a 75.2% improvement in bioenergy recovery and an 83.3% enhancement in net energy compared to the conventional system (primary sedimentation and anaerobic digestion). This self-reliant and novel process can be applied in municipal wastewater treatment to advance energy neutrality at a lower cost.